Disorders related to sexuality and gender identity in the ICD‐11: revising the ICD‐10 classification based on current scientific evidence, best clinical practices, and human rights considerations. Issue 3 (22nd September 2016) - Reed, Geoffrey M.; Drescher, Jack; Krueger, Richard B.; Atalla, Elham; Cochran, Susan D.; First, Michael B.; Cohen‐Kettenis, Peggy T.; Arango‐de Montis, Iván; Parish, Sharon J.; Cottler, Sara; Briken, Peer; Saxena, Shekhar
Abstract : In the World Health Organization's forthcoming eleventh revision of the International Classification of Diseases and Related Health Problems (ICD‐11), substantial changes have been proposed to the ICD‐10 classification of mental and behavioural disorders related to sexuality and gender identity. These concern the following ICD‐10 disorder groupings: F52 Sexual dysfunctions, not caused by organic disorder or disease; F64 Gender identity disorders; F65 Disorders of sexual preference; and F66 Psychological and behavioural disorders associated with sexual development and orientation. Changes have been proposed based on advances in research and clinical practice, and major shifts in social attitudes and in relevant policies, laws, and human rights standards. This paper describes the main recommended changes, the rationale and evidence considered, and important differences from the DSM‐5. An integrated classification of sexual dysfunctions has been proposed for a new chapter on Conditions Related to Sexual Health, overcoming the mind/body separation that is inherent in ICD‐10. Gender identity disorders in ICD‐10 have been reconceptualized as Gender incongruence, and also proposed to be moved to the new chapter on sexual health. The proposed classification of Paraphilic disorders distinguishes between conditions that are relevant to public health and clinical psychopathology and those that merely reflect private behaviour. ICD‐10 categories related to sexual orientation have been recommended for deletion from the ICD‐11.